First observation of the Λ0b → D+D−Λ decay - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Frau, Giulia; Glaser, Fabian; Günther, Paul André; et al. (Journal of high energy physics, 2024)
The Λ0b→ D+D−Λ decay is observed for the first time using proton-proton collision data collected by the LHCb experiment at a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 5.3 fb−1. Using the B0 → D+D-K0S decay as a reference channel, the product of the relative production cross-section and decay branching fractions is measured to be R = σΛ0bσB0×B(Λ0b → D+D−Λ)B(B0 → D+D−K0S) = 0.179 ± 0.022 ± 0.014 , where the first uncertainty is statistical and the second is systematic. The known branching fraction of the reference channel, B(B0 → D+D−K0S), and the cross-section ratio, σΛ0 b /σB0 , previously measured by LHCb are used to derive the branching fraction of the Λ0 b → D+D−Λ decay B(Λ0b → D+D−Λ) = (1.24 ± 0.15 ± 0.10 ± 0.28 ± 0.11) × 10−4 , where the third and fourth contributions are due to uncertainties of B(B0 → D+D−K0S) and σΛ0b /σB0 , respectively. Inspection of the D+Λ and D+D− invariant-mass distributions suggests a rich presence of intermediate resonances in the decay. The Λ0b → D∗+D−Λ decay is also observed for the first time as a partially reconstructed component in the D+D−Λ invariant mass spectrum.
Im Titel sind die Zahl "0" und die Zeichen "+" und "-" hochgestellt und der Buchstabe "b" ist tiefgestellt
The LHCb collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C. Cocha Toapaxi, M. De Cian, L. Dittmann, S. Esen, G. Frau, F.C. Glaser, P.A. Günther, X. Han, S. Hausmann-Menzemer, P. Herrero Gascon, J. Hu, J. Kubat, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, P.R. Pais, S.R. Roy, M. Ruiz Diaz, M. Schmelling, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov und weitere 1059
Gesehen am 14.07.2025